1999
DOI: 10.1080/10715769900300721
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diabetic polyneuropathy with the antioxidant thioctic acid (α-lipoic acid): A two year multicenter randomized double-blind placebo-controlled trial (ALADIN II)

Abstract: Short-term trials with the antioxidant thioctic acid (TA) appear to improve neuropathic symptoms in diabetic patients, but the long-term response remains to be established. Therefore, Type 1 and Type 2 diabetic patients with symptomatic polyneuropathy were randomly assigned to three treatment regimens: (1) 2 x 600(mg of TA (TA 1200), (2) 600)mg of TA plus placebo (PLA) (TA 600) or (3) placebo and placebo (PLA). A trometamol salt solution of TA of 1200 or 600 mg or PLA was intravenously administered once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
3
23

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(160 citation statements)
references
References 37 publications
3
127
3
23
Order By: Relevance
“…The safety of each of the four compounds used in this study has been previously assessed in humans. 1,5,12,13,29,32,38,47,49 Consequently, we did not make extensive measurements of safety. However, we did monitor animal body weight, body condition, and eating behavior daily throughout the intervention, and organs were inspected by a pathologist for gross morphological abnormalities at the time of sacrifice.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of each of the four compounds used in this study has been previously assessed in humans. 1,5,12,13,29,32,38,47,49 Consequently, we did not make extensive measurements of safety. However, we did monitor animal body weight, body condition, and eating behavior daily throughout the intervention, and organs were inspected by a pathologist for gross morphological abnormalities at the time of sacrifice.…”
Section: Animalsmentioning
confidence: 99%
“…17,44 In humans, ␣-LA supplementation reduced low-density lipoprotein oxidative damage 27 and improved nerve function in diabetic neuropathy. 38 Additionally, ␣-LA enhances CrM uptake in young healthy males, 5 an effect that may be relevant in DMD where oxidative stress is increased. 39 Interestingly, a weaker antioxidant, green tea extract, reduced muscle necrosis and regeneration in the fast-twitch muscle of mdx mice.…”
mentioning
confidence: 99%
“…The ALADIN and SID-NEY clinical trials of LA showed that its oral or intravenous administration improves nerve conduction velocity and neuropathic symptoms, such as pain, burning, paresthesia, and numbness (42)(43)(44)(45). To date, the therapeutic use of LA in the treatment of diabetic polyneuropathies remains the best documented and the most significant benefit of LA to human health.…”
Section: Clinical Applications Of Lamentioning
confidence: 99%
“…Though another study measured nerve conduction velocities, its outcomes of sural SNCV and tibial MNCV were based on given ALA i.v. for 5 days followed by long-term oral supplement (12). All these above studies were excluded.…”
Section: Description Of the Studiesmentioning
confidence: 99%